Rhino-Orbito-Cerebral Mucormycosis: Two Cases with Amaurosis as Presentation, Medical Surgical Management and Follow-Up - Carmen Navarro-Perea; Ignacio Cañas-Zamarra; Enrique Mencía-Gutiérrez; Enrique Revilla-Sánchez; María-Dolores Lago-Llinás; Silvia Pérez-Trigo; Álvaro Bengoa-González (Case Reports in Ophthalmological Medicine)
Purpose: Mucormycosis is an infection caused by fungi to the class Zygomycetes that usually appears in immunosuppressed patients. Diagnostic confirmation is often delayed, with fatal prognosis in cases in which treatment is not rapidly established. Case report: We present two clinical cases of rhino-orbito-cerebral mucormycosis with an atypical presentation form, consisting of a unilateral complete sudden vision loss. Intravenous treatment with liposomal amphotericin B was started and total orbital exenteration surgery was performed. The removed surgical area was filled with gauze impregnated with liposomal amphotericin B and was left open for cures every 12 hours. Due to the good clinical evolution, a reconstruction of the orbital exenteration defect was performed in Case 1 with a temporal muscle flap and a skin island pedicled flap. In Case 2, reconstruction was not performed due to the poor evolution of the patient. Discussion: As it is a very aggressive surgery, the aesthetic and functional sequelae are very important. When the survival of the patient is achieved, we should offer reconstructive solutions that improve their quality of life. The reconstruction carried out using a flap of the temporal muscle can be made in a single act without requiring microvascular surgery.